Test cases for commissioning an add-on micro multi-leaf collimator Apex for stereotactic radiosurgery treatments - Pérez Curbelo, Javier; Diaz Moreno, Rogelio; Caballero Pinelo, Roberto (Revista Brasileira de Física Médica, 2020)
Two comprehensive test cases are presented for dosimetric commissioning of a radiosurgery system, in a hospital where dedicated phantoms are not available. The system consisted of an Elekta Precise linear accelerator, an Apex micro multi-leaf collimator, and a Monaco treatment planning system (TPS). The purpose of Test I was to assess the dose accuracy with coplanar arc beams. Test II was an end-to-end type test, a rigid Leksell stereotactic frame was fixed to a watermelon phantom and Ergo++ TPS was used for stereotactic coordinates definition. The purpose of Test II was to assess the dose accuracy with non-coplanar arc beams and the influence of geometrical accuracy in the whole process. Ionization chambers were used for dose measurements. Results of Test I showed that discrepancies below 1% are achievable, while results of Test II allowed detection of geometric shifts < 1 mm with dose discrepancies lower than 1%. To the best of our knowledge, there are not published works reporting test cases for commissioning a stereotactic radiosurgery system like the one tested in this work. The designed test cases showed adequacy for assessment of TPS accuracy in complex treatment configurations, like those used in stereotactic radiosurgery.